Correlation between personality traits and acoustic patterns in the speech of spanish speaking individuals in the river plate (2023)
The background of this study is presented in three sections: a) Motivation Theories and their relationship with brain structures, b) Psychometric studies of Primary Personality Factors (PPF) and c) The role of brain structures in the production of prosodic aspects of language. Its objective is to evaluate the combination of parameters and acoustic characteristics found in the speech of normal individuals (n = 23), previously grouped according to a psychometric study of their personality in order to sort out Primary Personality Factors (PPF) and improve our knowledge on Human Temperaments. Acoustic parameters under study were: fundamental frequency (F0), total maximum energy and total duration, normal constituents of prosodic information. A three-syllable same phrase was analyzed in all the cases. The subject´s emissions were registered on a Sony (WM – 6 × 320) recorder and the phrase studied for each individual (N = 22) was processed with the Anagraf speech acoustic analysis program. The acoustic characteristics more useful to discriminate between PPF groups are: a) F0 rank and b) energy differences between stressed syllables and those not stressed. Acoustic studies can complement psychometric ones in order to differentiate each PPF group